Field Evaluation of Cocksfoot, Tall Fescue and Phalaris for Dry Marginal Environments of South‐Eastern Australia. 2. Persistence. (30th July 2015) - Culvenor, R. A.; Clark, S. G.; Harris, C. A.; Hayes, R. C.; Li, G. D.; Nie, Z. N.; Norton, M. R.; Partington, D. L.
Abstract: Perennial grasses provide forage and environmental benefits in the agricultural systems of southern Australia, but persistent cultivars are lacking for the lower rainfall inland margins (<600 mm average annual rainfall). Potential new cultivars of cocksfoot ( Dactylis glomerata L.), tall fescue ( Festuca arundinacea Schreb. = syn. Lolium arundinaceum (Schreb.) Darbysh.) and phalaris ( Phalaris aquatica L.) have been developed in response to this need. These and older cultivars were evaluated for persistence at five sites in south‐eastern Australia from 2009 to 2013. A wide range in rainfall was experienced, but survival was principally reduced by a severe spring–summer–autumn drought in the final year in which all species began to decline in persistence once the spring 2012 to autumn 2013 cumulative climatic moisture deficit became higher than about 700 mm and declined very severely at deficits over 1000 mm. The highly summer‐dormant cocksfoot ssp. hispanica control cultivar Kasbah showed outstanding survival of this event in the cropping zone of southern New South Wales, but not at the drier of two sites with acidic soils in central Victorian where all cocksfoot cultivars showed similar survival. Potential new summer‐active tall fescue cultivars survived well at the higher rainfall Victorian site and under high rainfall in northern NSW. All tall fescue cultivars experienced high mortality during a period of high moisture stress in the spring of the establishment year in southern NSW, but the Mediterranean cultivar Grasslands Flecha MaxP gradually recovered. Differences among phalaris cultivars were not large with new cultivars of North African origin being marginally more persistent at the drier site in southern NSW. Comparisons with results from the Mediterranean Basin are discussed. Although there was no clear evidence of differences in persistence between the new and old cultivars, some of the new cultivars were considered to show potential for commercial release.